(3GdgOGjI TQM GdHOGjIs - (3GdnerQpZjfGfj GdaQZGfj, CHh GdMSf, HQgGf GdOjf, Ydj Hf CHj HcQ Hf YHO GdLdjd, (B593 (3g`s ((3GdeOQSI GdfhQjI HOeTb , HGH GdNhGUjfs)
(3ChdgG (B:s
( (3cJGH GdWgGQI (B) (3GdMeO ddg GdPj CYdi eYGde GdYde hCYdGeg hbOQi Ydi GdhYL aj eHOC HOGjI GdeHJOj Cf CTQMgG aUQaJ GdYfGf hGdYfGjI Edi TQM BNQ ehShe HGdgOGjI CLeY ajg HJhajb Gddg JYGdi Hjf YfhGf GdQhGjI heJhf GdOQGjI s
(3BNQgG (B:s
( (3cJGH GdHjhY (B) (3aUd hEPG Hfi eSLOG de jRd edcg Yfg MJi jaQRg Yf edcg aEf Cgd GdYQa jQjOhf HPdc aj GdZdI GdabQGA haj ZjQgG GdJShjI Hjfge hHjf GdCZfjGA hdCf GdMGLI JTed GdabjQ hGdZfj aj GdTQH hGdZfj dG jMJGL Edi gPg GdZdI dZfGFg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 266s
(3eYLe GdeDdajf (B2 / 411s
(3cTa GdXfhf (B2 / 2031s
(3gOjI GdYGQajf (B1 / 702s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs